Proceedings of the 2017 ACM on Web Science Conference 2017
DOI: 10.1145/3091478.3091513
|View full text |Cite
|
Sign up to set email alerts
|

Using Facebook Ads Audiences for Global Lifestyle Disease Surveillance

Abstract: Every day, millions of users reveal their interests on Facebook, which are then monetized via targeted advertisement marketing campaigns. In this paper, we explore the use of demographically rich Facebook Ads audience estimates for tracking non-communicable diseases around the world. Across 47 countries, we compute the audiences of marker interests, and evaluate their potential in tracking health conditions associated with tobacco use, obesity, and diabetes, compared to the performance of placebo interests. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 16 publications
0
64
0
Order By: Relevance
“…Seminal works using this approach focused on the health domain [31,39]. For example, Araújo et al [3] extracted data in 47 countries to track health conditions associated with lifestyle diseases. They showed that, within each country, Facebook data could provide insights into different trends of health awareness across demographic groups.…”
Section: Related Workmentioning
confidence: 99%
“…Seminal works using this approach focused on the health domain [31,39]. For example, Araújo et al [3] extracted data in 47 countries to track health conditions associated with lifestyle diseases. They showed that, within each country, Facebook data could provide insights into different trends of health awareness across demographic groups.…”
Section: Related Workmentioning
confidence: 99%
“…Information is extracted from the API programmatically using the language Python, and in particular, the module pySocialWatcher (Araujo et al. ).…”
Section: Datamentioning
confidence: 99%
“…We use the Ads Manager application, Facebook's Marketing Application Programming Interface (API), to extract estimates of potential reach over time. Information is extracted from the API programmatically using the language Python, and in particular, the module pySocialWatcher (Araujo et al 2017).…”
Section: Datamentioning
confidence: 99%
“…For example, Araújo et al (2017) tracked the size of audiences in Facebook with interests that could be markers of tobacco use, obesity, or diabetes. Although their results were negative—meaning that they found that differences in interest audiences were only weakly indicative of the corresponding prevalence rates—they developed an analysis approach that can be used in other contexts.…”
Section: “Digital Census”: Facebook Ads Manager Data As a Case Studymentioning
confidence: 99%
“…The premise of creating a baseline was to control for the amount of time and number of searches people generally conduct on Facebook. In other words, Araújo et al (2017) used a form of normalization for behavioral features of Facebook users. Developing tools to standardize compositional changes in the population of Facebook users is another area where demographers can develop methodological advances.…”
Section: “Digital Census”: Facebook Ads Manager Data As a Case Studymentioning
confidence: 99%